Phenotyping sarcoidosis: a single institution retrospective analysis - Bertuccio, Francesco Rocco; Piloni, Davide; Russo, Marianna; Tousa, Fady; Crescenzi, Mariachiara; Putignano, Paola; Baio, Nicola; Maragò, Ida; Corsico, Angelo Guido; Stella, Giulia Maria (Frontiers in Medicine, 2025)
IntroductionSarcoidosis is a systemic disorder marked by the presence of non-caseating epithelioid cell granulomas. The diagnosis relies on a consistent clinical presentation, histological evidence of non-necrotizing granulomatous inflammation in one or more tissue specimens, and the exclusion of other potential etiologies of granulomatous disease. It is a heterogeneous disease with many focal points to be clarified. For instance, finding a relationship between symptom burden, race, gender, HRQoL, and pulmonary function could have therapeutic ramifications, influence clinical practice, and aid in selecting patients for specific clinical studies.MethodsA comprehensive statistical evaluation was conducted using the JMP partitioning algorithm which explores all potential divisions to identify the most predictive variables.ResultsWith our analysis, we tried to categorize patients from a single Institution respiratory unit to delineate clinical phenotypes in sarcoidosis.ConclusionsLarger studies using appropriate methodology should surely be carried out to address this issue and help clarify the varying contributions of genetics, socioeconomic status, environmental exposures, and other sociodemographic factors to illness severity and phenotypic presentation. Additionally, the application of transcriptomics, interdisciplinary methods, patients' disease perspectives, and the publishing of novel discoveries may contribute to enhanced clinical support and a deeper comprehension of the etiology of illness.